High Burden of Human Papillomavirus Infection in Madagascar: Comparison With Other Sexually Transmitted Infections. (31st January 2018) - Bigoni, Jérôme; Catarino, Rosa; Benski, Caroline; Viviano, Manuela; Munoz, Maria; Tilahizandry, Honoré; Petignat, Patrick; Vassilakos, Pierre
Background: In Madagascar, human papillomavirus (HPV), human immunodeficiency virus (HIV), and hepatitis B virus (HBV) infection, as well as syphilis share common risk factors but seem to differ in their prevalence. We measured and compared their prevalence in the country. Methods: The data used in this study came from the Saint Damien Health Centre in Ambanja, Madagascar. The tests used for disease detection were the Alere Determine, Virucheck, rapid plasma reagin, and S-DRY self-HPV samples for HIV infection, HBV infection, syphilis, and HPV infection, respectively. Results: In men and women, respectively, the prevalence was 0.6% and 0.4% for HIV infection, 2.2% and 2.0% for HBV infection, and 0.6% and 0.3% for syphilis. The HPV infection prevalence was 39.3%. Conclusions: Despite common risk factors, the prevalence of HPV infection was high, in contrast to a much lower prevalence of other sexually transmitted infections (STIs) in the same geographical area. Further investigations are required to clarify the status of STIs in the Malagasy population.